You are on page 1of 2

m

a pa q=a pp
( a p )q=a pq
a p ap
( ) = p
b
b

a m=a n
1

an=a n

a Pa q=a pq
(ab) p=a pa p
(a > 0; b > 0)

(a > 0; b > 0)


log a (bc)=log a b+ log a c
b
log a ( )=log a blog a c
c
log a b r=rlog a b

a log a b=b
a log a c =c

30

45

60

90

180

270

3
2

sin, cos, tg, ctg


tg actg a=1
sin 2 a+ cos 2 a=1
2
1
sin a= 1cos a
tg a=
ctg a
cos a= 1sin2 a
1
ctg a=
tg a

1
cos 2 a
1
1+ ctg 2 a= 2
sin a
2

1+ tg a=

sin, cos tg a -a
sin(a )=sina

cos (a)=cos a

tg (a)=tg a

ctg (a)=ctga


cos (a+ b)=cos acos bsin asin b

cos (ab)=cos acos b+ sin asin b

sin(a+ b)=sin acos b+ cos asin b

sin(ab)=sin acos bcos asin b

tg (a+ b)=

tg a+ tg b
1tg atg b

sin 2 a=2 sin acos a

cos 2 a=cos 2 asin 2 a

tg 2 a=

2tg a
1tg 2 a

U =

S ( t+ h)S (t ) g
= ((t+ h)2t 2 )
h
2h

U =lim
h 0

S ( t+ h)S (t )
h


( x p )' = px p1
(( kx+ b) p) '=kp(kx+ b) p1

C ' =0

(x )'=1

(x 2 )' =2x

(x 3 )' =3x 2

1
1
( )' = 2 ( x0)
x
x


( f (x )+ g ( x))' = f ' ( x)+ g ' ( x)
( f ( x )g ( x))' = f ' (x )g ( x)+ f ( x)g ' ( x )

( x) '=

1
2 x

( x> 0)

(c f ( x )) ' =c f ' (x )
(

f ( x)
f ' ( x)g (x) f ( x )g ' ( x)
)' =
g (x )
g2( x )


k =tg a= f ' (x )

- :
1.
2.
3.
4.
5.